Wounaan medicine in forced displacement: among forgetfulness and memory - Gonzalez Guerrero, Andrea (Universidad Distrital Francisco José de Caldas, 2016)
Since 2003 the Wounaan indigenous community located in the department of Choco and Valle del Cauca (Colombia) has been displaced due to the armed conflict in the country and the seeking of better economic conditions. Their way of life, the exercise of their medicine, the representations and practices in health have been affected by the territorial rootlessness and lack of natural resources. By means of the participant observation and interviews compiled between 2014 and 2015, this article describes and analyses, how the bogotano context affects Wounaan care system, what is the role of Wounaan medical figures within this context of mobility, and finally, what medical values are transformed into the migration.